POST-EVACUATION OF SILICONE OIL COMPLICATIONS IN RHEGMATOGENOUS RETINAL DETACHMENT PATIENTS WHO UNDERWENT PARS PLANA VITRECTOMY AT TERTIARY HOSPITAL IN BALI, INDONESIA - Andayani, Ari; Wibawa, I Made Dwi Surya; Suryathi, Ni Made Ari; Triningrat, Anak Agung Mas Putrawati; Manuaba, Ida Bagus Putra (Indonesian Vitreoretinal Society, 2023)
Introduction: Pars plana vitrectomy with silicone oil injection has become a standard procedure to treat retinal detachment with complex cases. Considerations related to the use of silicone oil are the need for additional surgical procedures to remove silicone oil after the retinal condition is declared stable or because emulsification of silicone oil has occurred. Methods: An analytical observational study with a cross-sectional approach. Data were collected retrospectively by collecting medical records of patients who underwent silicone oil evacuation in 2021. Result: The research subjects were 23 people, where 52.2% of the subjects were women with a median age of 51 years. Most of the subjects (65.2%) had no complications, with the most complications occurring were secondary glaucoma (13%) and redetached retina (13%). There was no statistically significant difference between visual acuity before and after the evacuation of silicone oil with a P value of 0.202 and there was no statistically significant difference between IOP before and after evacuation of silicone oil with a P value of 0.132. Conclusion: Evacuation of silicone oil is a follow-up action after PPV with SO tamponade. Complications which may arise are detach dan glaucoma. There was no significant difference in visual acuity and IOP before and after SO evacuation.